Extracellular synthesis of silver nanoparticles using dried leaves of pongamia pinnata (L) pierre - Raut, Rajesh W.; Kolekar, Niranjan S.; Lakkakula, Jaya R.; Mendhulkar, Vijay D.; Kashid, Sahebrao B. (Nano-Micro Letters, 2010)
Extract of oven dried leaves of Pongamia pinnata (L) Pierre was used for the synthesis of silver nanoparticles. Stable and crystalline silver nanoparticles were formed by the treatment of aqueous solution of AgNO3 (1mM) with dried leaf extract of Pongamia pinnata (L) Pierre. UV-visible spectroscopy studies were carried out to quantify the formation of silver nanoparticles. Transmission electron microscopy, X-ray diffraction and Fourier transform infrared spectroscopy were used to characterize the silver nanoparticles. TEM image divulges that silver nanoparticles are quite polydispersed, the size ranging from 20 nm to 50 nm with an average of 38 nm. Water soluble heterocyclic compounds such as flavones were mainly responsible for the reduction and stabilization of the nanoparticles. Silver nanoparticles were effective against Escherichia coli (ATCC 8739), Staphylococcus aureus (ATCC 6538p), Pseudomonas aeruginosa (ATCC 9027) and Klebsiella pneumoniae (clinical isolate). The move towards extracellular synthesis using dried biomass appears to be cost effective, eco-friendly to the conventional methods of nanoparticles synthesis.